Efeito da acupuntura na dor e na qualidade de vida em mulheres com fibromialgia: um ensaio clínico randomizado - Baelz, Gustavo Urbanetto (2018)
Introduction: Fibromyalgia (FM) is a chronic generalized pain syndrome, which causes disability and loss of quality of life. Treatment involves the use of medications, education, and exercise. Another therapeutic resource used to reduce the symptoms of FM is acupuncture. Objective: To evaluate the efficacy of acupuncture in pain and quality of life in women with FM. Methods: Thirty-two women with FM diagnosis were selected according to the classification criteria of the American College of Rheumatology. Participants were randomized into two groups: treatment with acupuncture (n = 17) and simulated acupuncture (n = 15). Interventions occurred once a week, lasting 30 minutes each, for four weeks. The outcomes were measured by Visual Analogue Scale (VAS); the Fibromyalgia Impact Questionnaire (FIQ) and algometry before and immediately after the last session. Results: There was no significant difference in the VAS in both groups (p> 0.05). In the FIQ the acupuncture group reduced the total score in 24.31% (p <0.001) and in the items: work done (p <0.001), pain (p <0.001), fatigue (p <0.001), tiredness (p<0.05) and depression (p <0.05); in the simulated acupuncture group there was a reduction of 18.84%, but it was not significant (p> 0.05). In the algometry the results were not significant in both groups (p> 0.05). Conclusion: Acupuncture improved quality of life in women with FM but did not demonstrate efficacy in reducing pain and increasing pressure pain threshold.